ENSURING THE SAFETY OF TOURIST AMENITIES AND INSURANCE ITEMS TO PREVENT EVENTS IN THE FIELD OF TOURISM (ResearchJet Journal of Analysis and Inventions, 2021)
The article highlights the role of travel insurance in a growing market economy in ensuring the safety of tourists, the problems that insurance companies face in solving this problem and the measures taken to develop travel insurance in the country.